PO156 The impact of neuromyelitis optica spectrum disorder on driving. (1st December 2017) - Linaker, Sam; Mutch, Kerry; Whittam, Daniel; Hamid, Shahd; Jacob, Anu
Abstract : Background: NMOSD is well known to cause physical disability, however the impact on a patient's life and work is poorly quantified. One important aspect of this is being unable to drive. No data exists on the proportion of patients affected. Method: A cross-sectional study was conducted in 103 (84 female) patients with aquaporin-4 antibody positive NMOSD, of driving age (median age 53). Each patient was questioned about their driving status before onset of NMOSD and at present. Results: 71/103 (73.1%) patients were driving before first attack. 6/103 (6%) patients never held a licence due to disability from NMOSD. Of those who were driving, 33/71 (46%) stopped. Of these 19/33 (58%) of patients said this was due to the effects of transverse myelitis (TM), 10/33 (30%) attributed it to optic neuritis (ON) whilst 2/33 (6%) reported it was due to both and a further 2/33 (6%) cited confidence issues. Conclusion: 38% of patients are not able to drive due to the direct effects of NMOSD, with significant impacts on work, lifestyle and independence, highlighting the need to aggressively treat the disease early on.